CpG Methylation of DNA Restricts Prereplication Complex Assembly in Xenopus Egg Extracts - Harvey, Kevin J. (American Society for Microbiology, 2003)
In a Xenopus egg replication system, the origin recognition complex (ORC) does not bind to CpG methylated DNA and DNA replication is inhibited. Insertion of low density CpG DNA of at least 1.2 kb into methylated plasmids rescues both replication and ORC binding. Using this pseudo-origin, we find that ORC binding is restricted to low-CpG-density DNA; however, MCM is loaded onto both weakly and highly methylated DNA and occupies at least ∼2 kb of DNA. Replication initiates coincident with MCM, and even the most distally bound MCM is associated with sites of replication initiation. These results suggest that in metazoans MCM is loaded onto and initiates replication over a large region distant from ORC.